Handbook of research on new media, training, and skill development for the modern workforce - Mentor, Dominic, 1968- (Advances in multimedia and interactive technologies (AMIT) book series., 2022)
"The forced abrupt shift to online learning during the COVID pandemic revealed needs for the adoption and use of new media, virtual training, as well as online skill development for the modern workforce and this book a variety of tools to help readers to rapidly incorporate new media tools into their teaching and learning environments"--